Systematic CHAAOS: Teaching Vocabulary in English/Language Arts Special Education Classes in Middle School - O’Connor, Rollanda E.; Sanchez, Victoria M.; Jones, Brian T.; Suchlit, Luisana; Youkhanna, Valencia; Beach, Kristen D.; Widaman, Keith (Journal of learning disabilities, 2021)
In this multi-year study, we taught English/Language Arts teachers of students with learning disabilities in middle school to incorporate 15 min of daily vocabulary activities with students in their intact special education English/Language Arts classes. During Year 1, teachers taught 48 words to their sixth grade students, who learned and retained the words significantly better than the students in business-as-usual (BAU) control classes. In the current study, we report the second year results, as the sixth grade students entered seventh grade. Students (n = 42) in treatment classes again learned 48 new vocabulary words significantly better than similar students in BAU (n = 21) special education classes. In seventh grade, students also outperformed BAU students on maintenance of these age-appropriate words (p < .001) and on a standardized measure of vocabulary (p = .04).